Anéis quânticos em grafeno na presença de defeitos topológicos - Silva Neto, José Amaro da (2013)
The Graphene is a two-dimensional(2-D) semiconductor crystal with null gap, where charge carriers behave as massless particles. In this speci c dynamics in the limit of low energies, the energy dispersion relation is linear, and this material can be described by massless Dirac equation contrasts with the semiconductors, for which the charge carriers are massive. In this framework, there is the problem of the electronic con nement in graphene because of tunneling. For overcome this di culty, is proposed a new model of quantum ring, based on Dirac oscillator and models of rings Tan-Inkson and Bakke- Furtado. From this new coupling, are obtainable the energy spectrum, persistent currents and positive spinors to a graphene sheet with / without topological defect type disclination by massless Dirac equation (2+1).